A Risk Score Including Carotid Plaque Inflammation and Stenosis Severity Improves Identification of Recurrent Stroke. Issue 3 (March 2020) - Kelly, Peter J.; Camps-Renom, Pol; Giannotti, Nicola; Martí-Fàbregas, Joan; McNulty, Jonathan P.; Baron, Jean-Claude; Barry, Mary; Coutts, Shelagh B.; Cronin, Simon; Delgado-Mederos, Raquel; Dolan, Eamon; Fernández-León, Alejandro; et al.
Abstract : Background and Purpose—: In randomized trials of symptomatic carotid endarterectomy, only modest benefit occurred in patients with moderate stenosis and important subgroups experienced no benefit. Carotid plaque 18 F-fluorodeoxyglucose uptake on positron emission tomography, reflecting inflammation, independently predicts recurrent stroke. We investigated if a risk score combining stenosis and plaque 18 F-fluorodeoxyglucose would improve the identification of early recurrent stroke. Methods—: We derived the score in a prospective cohort study of recent (<30 days) non-severe (modified Rankin Scale score ⩽3) stroke/transient ischemic attack. We derived the SCAIL (symptomatic carotid atheroma inflammation lumen-stenosis) score (range, 0–5) including 18 F-fluorodeoxyglucose standardized uptake values (SUVmax <2 g/mL, 0 points; SUVmax 2–2.99 g/mL, 1 point; SUVmax 3–3.99 g/mL, 2 points; SUVmax ≥4 g/mL, 3 points) and stenosis (<50%, 0 points; 50%–69%, 1 point; ≥70%, 2 points). We validated the score in an independent pooled cohort of 2 studies. In the pooled cohorts, we investigated the SCAIL score to discriminate recurrent stroke after the index stroke/transient ischemic attack, after positron emission tomography-imaging, and in mild or moderate stenosis. Results—: In the derivation cohort (109 patients), recurrent stroke risk increased with increasing SCAIL score ( P =0.002, C statistic 0.71 [95% CI, 0.56–0.86]). The adjusted (age, sex, smoking, hypertension, diabetes mellitus, antiplatelets, and statins) hazard ratio per 1-point SCAIL increase was 2.4 (95% CI, 1.2–4.5, P =0.01). Findings were confirmed in the validation cohort (87 patients, adjusted hazard ratio, 2.9 [95% CI, 1.9–5], P <0.001; C statistic 0.77 [95% CI, 0.67–0.87]). The SCAIL score independently predicted recurrent stroke after positron emission tomography-imaging (adjusted hazard ratio, 4.52 [95% CI, 1.58–12.93], P =0.005). Compared with stenosis severity (C statistic, 0.63 [95% CI, 0.46–0.80]), prediction of post-positron emission tomography stroke recurrence was improved with the SCAIL score (C statistic, 0.82 [95% CI, 0.66–0.97], P =0.04). Findings were confirmed in mild or moderate stenosis (adjusted hazard ratio, 2.74 [95% CI, 1.39–5.39], P =0.004). Conclusions—: The SCAIL score improved the identification of early recurrent stroke. Randomized trials are needed to test if a combined stenosis-inflammation strategy improves selection for carotid revascularization where benefit is currently uncertain. Abstract : Supplemental Digital Content is available in the text.